Shared Transcriptional Control and Disparate Gain and Loss of Aphid Parasitism Genes. (25th August 2018) - Thorpe, Peter; Escudero-Martinez, Carmen M; Cock, Peter J A; Eves-van den Akker, Sebastian; Bos, Jorunn I B
Abstract: Aphids are a diverse group of taxa that contain agronomically important species, which vary in their host range and ability to infest crop plants. The genome evolution underlying agriculturally important aphid traits is not well understood. We generated draft genome assemblies for two aphid species: Myzus cerasi (black cherry aphid) and the cereal specialist Rhopalosiphum padi . Using a de novo gene prediction pipeline on both these, and three additional aphid genome assemblies ( Acyrthosiphon pisum, Diuraphis noxia, and Myzus persicae ), we show that aphid genomes consistently encode similar gene numbers. We compare gene content, gene duplication, synteny, and putative effector repertoires between these five species to understand the genome evolution of globally important plant parasites. Aphid genomes show signs of relatively distant gene duplication, and substantial, relatively recent, gene birth. Putative effector repertoires, originating from duplicated and other loci, have an unusual genomic organization and evolutionary history. We identify a highly conserved effector pair that is tightly physically linked in the genomes of all aphid species tested. In R. padi, this effector pair is tightly transcriptionally linked and shares an unknown transcriptional control mechanism with a subset of ∼50 other putative effectors and secretory proteins. This study extends our current knowledge on the evolution of aphid genomes and reveals evidence for an as-of-yet unknown shared control mechanism, which underlies effector expression, and ultimately plant parasitism.